Characteristics of HCV co-infection among HIV infected individuals from an area with high risk of blood-borne infections in central China. - Tiejun Zhang; Damien C Tully; Sujuan Zhou; Na He (PLoS ONE)
Objective Hepatitis C virus (HCV) and human immunodeficiency virus (HIV) co-infection has been proved to be a growing public health concern. The prevalence and genotypic pattern vary with geographic locations. Limited information is available to date with regard to HCV genotype and its clinical implications among those former commercial blood donor communities. The aims of this study were to genetically define the HCV genotype and associated clinical characteristics of HIV/HCV co-infected patients from a region with commercial blood donation history in central China. Methods A cross sectional study, including 164 HIV infected subjects, was conducted in Shanxi province central China. Serum samples were collected and HCV antibody testing, AST and ALT testing were performed. Seropositive samples were further subjected to RT-PCR followed by direct sequence coupled with phylogenetic analysis of Core-E1 and NS5B regions performed in comparison with known reference genotypes. Findings A total of 139 subjects were HCV antibody positive. Genotype could be determined for 88 isolates. Phylogenetic analysis revealed that the predominant circulating subtype was HCV 1b (65.9%), followed by HCV 2a (34.1%). The HCV viral load in the subjects infected with HIV1b was significantly higher than those infected with HCV 2a (P = 0.006). No significant difference for HCV RNA level was detected between ART status, CD4+ cell count level and HIV RNA level. Serum AST and ALT level were likely to increase with HCV RNA level, although no significance was observed. Those who had conducted commercial donation later than 1991 (OR 3.43, 95% CI: 1.12-10.48) and had a short duration of donation (OR 0.35, 95% CI: 0.13-0.96) were more likely to be infected with HCV 1b. Conclusion These results suggest that HCV subtype 1b predominates in this population, and the impact of HIV status and ART on HCV disease progression is not significantly correlated.